Exploitation of Plasmon resonance phenomenon for the improvement of direct absorption solar collector performance / Abdul Rahman Mallah - Abdul Rahman , Mallah (2021)
Direct absorption solar collectors (DASCs) are distinguished from other solar collectors by the volumetric absorption process, where the working fluid directly absorbs solar radiation. Studies have shown that DASCs can increase energy conversion efficiency by ~10% compared with conventional solar collectors. With advances in the development of nanotechnology, the concept of volumetric absorption is now feasible. Advances in nanotechnology accompanied by phenomenal discoveries at the nanoscale have made it possible to produce plasmonic materials. Plasmonic materials exhibit distinct optical characteristics under specific conditions. The free-electron cloud of metallic nanoparticles oscillates harmonically with the incident radiation. At a particular wavelength, resonance occurs between the collective oscillations of electrons and the incident electromagnetic waves, which intensifies the photo-thermal energy conversion at the resonance conditions. This phenomenon is known as localized surface plasmon resonance (LSPR), which gives exceptional absorption efficiency for plasmonic nanoparticles at the resonance wavelength. There is great potential to use plasmonic nanoparticles in the direct absorption solar collectors. This study provides insight into the LSPR phenomenon of silver nanostructures and an innovative technique is proposed to exploit their capabilities to boost the efficiency of volumetric solar collectors. Silver nanoparticles exhibit LSPR with high intensity, which can be adjusted within a broad spectral band of 300–1,200 nm by tailoring the shape, size, and aspect ratio of the nanoparticles. In this study, the optical characteristics of various silver nano-morphologies were investigated to formulate blended nanofluids that can absorb solar irradiation within a broad spectral range. The finite element method has been implemented to determine the absorption efficiency of different silver nano-morphologies like silver nanospheres, nanorods, nanoplates and core/shell silver/silica nanocomposites. Also, the effects of the nanoparticles’ size and aspect ratio were extensively studied. The results were used to formulate a high-efficiency blended nanofluid with a very low volume fraction of silver nanoparticles. The simulation results revealed that the different silver nano-morphologies absorb efficiently at different solar spectrum bands. Silver nanospheres and nanoprisms with fine-tuned sizes and aspect ratios of 3–9 were synthesized and characterized. An innovative test section was built to validate the performance of different silver nano-morphologies under simulated solar irradiation. The test section allows the irradiance bands that have not been absorbed by the nanoparticles to escape from the collector instead of being absorbed or reflected by the bottom surface, unlike the test sections in conventional experiments. Hence, the photo-thermal conversion efficiency of nanofluids based on individual silver nano-morphologies can be accurately obtained. Five nanofluids were tested under three irradiation densities equivalent to 1, 1.5 and 2 suns. Three concentrations of each nanofluid were prepared and tested at varied Reynolds numbers ranging from around 150 to 750. The main contribution of this work is the formulation of blended nanofluids containing different silver nano-morphologies to efficiently absorb the broadband solar spectrum. The experimental results revealed the promising performance of the blended nanofluids, where the efficiency of the direct absorption solar collector exceeds 70% at a solar radiation concentrating factor of ~2 and a total nanoparticle concentration of 0.001 wt%. The interesting aspect of the blended nanofluids formulated in this study is the remarkable low volume fraction of the nanoparticles, which reduces settlement and agglomeration ratio. Consequently, a higher solar concentration ratio can be harnessed by using the blended plasmonic nanofluids with a relatively low loading of nanoparticles.